2000
DOI: 10.12693/aphyspola.97.867
|View full text |Cite
|
Sign up to set email alerts
|

Quasicritical Behaviour of the NMR and µSR Relaxation in YMn2Dx

Abstract: The magnetic and structural properties of YΜn 2 are strongly influenced by introduction of hydrogen (deuterium) in the structure, however, it only slightly modifies the noncollinear antiferromagnetic structure of the compound. The temperature dependences of the NMR relaxation times T1 and Τ2 of deuterium and the zero-field relaxation of muons in YΜn2 D x were measured at temperatures above the magnetic ordering temperature TN. The corresponding relaxation rates are described by the empirical expres- The C15 La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…16 The model of relaxation caused by spin fluctuations, introduced by Moriya, 17 gives for antiferromagnets, at temperatures close above the ordering temperature, the following expression for the spin-lattice relaxation rate: For the YMn 2 D x deuterides ͑hydrides͒ the muon 11 and NMR relaxation rates show divergence at the ordering temperature, but instead of Eq. ͑3͒ with fixed exponential factor 1/2, the formula with the free exponential factor may be used:…”
Section: B Relaxation Timesmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The model of relaxation caused by spin fluctuations, introduced by Moriya, 17 gives for antiferromagnets, at temperatures close above the ordering temperature, the following expression for the spin-lattice relaxation rate: For the YMn 2 D x deuterides ͑hydrides͒ the muon 11 and NMR relaxation rates show divergence at the ordering temperature, but instead of Eq. ͑3͒ with fixed exponential factor 1/2, the formula with the free exponential factor may be used:…”
Section: B Relaxation Timesmentioning
confidence: 99%
“…However, this behavior cannot be understood in terms of existing theories which predict that such divergences of critical type at the ordering temperature should not depend on chemical composition, and here in particular on the hydrogen ͑deuterium͒ concentration in the compound. This leads to the idea of the model, 16 which improves the Moriya's approach based on spin fluctuations. 17 The relaxation rates are generally proportional to ͚"(k)/⌫ k … term.…”
Section: B Relaxation Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic ordering temperature of cubic Laves phase compounds RMn 2 H x increases by more than 30% with hydrogen charging for 1.5 < x < 3.5 and R = Y, Dy, Tb, Gd [1][2][3][4]. Recently, we showed that the accompanying lattice expansion-and especially the increased Mn-Mn separation-changes also the quasi-critical behaviour reflected by µSR and 1 H/ 2 D nuclear spin-relaxation on approach to the antiferromagnetic ordering temperature of YMn 2 (H/D) x [5,6]. In this respect the nuclei on the tetrahedral interstitial sites with two R and two Mn nearest neighbours are convenient probes for the spin fluctuations and antiferromagnetic correlations on the Mn and R sublattices.…”
Section: Introductionmentioning
confidence: 94%
“…In this respect the nuclei on the tetrahedral interstitial sites with two R and two Mn nearest neighbours are convenient probes for the spin fluctuations and antiferromagnetic correlations on the Mn and R sublattices. Increased hydrogen content and Mn-Mn spacing increases not only the ordering temperature T N , but modifies also the wave-vector dependence of exchange interaction or dynamic susceptibility [5,6]. Structural distortions and ordered H/D superstructures are additional problems of these hydrides, however, that have to be considered for a complete magnetostructural phase diagram.…”
Section: Introductionmentioning
confidence: 99%